Trends in the Application of Postmastectomy Radiotherapy for Breast Cancer With 1 to 3 Positive Axillary Nodes and Tumors ≤5 cm in the Modern Treatment Era: A Retrospective Korean Breast Cancer Society Report - Chang, Jee Suk (Medicine (Baltimore), 2016)
Despite high-level evidence, the benefit of postmastectomy RT in these patients in recent years has not been fully elucidated. We investigated postmastectomy radiotherapy (RT) use and evaluated clinicopathologic and treatment factors influencing RT use in Korean women with pT1-2N1 breast cancer. We identified women diagnosed with pT1-2N1 breast cancer between 1994 and 2009 using the Korean Breast Cancer Registry. Factors associated with RT use were evaluated using logistic regression analysis. The median follow-up was 95 months. Of the 6196 women, 11.9% underwent postmastectomy RT. RT was applied more frequently in women with 3 positive lymph nodes (adjusted odds ratio [OR], 2.69) and larger tumors (OR per centimeter, 1.10). RT use was not significantly associated with well-established risk factors (e.g., tumor grade, hormone receptor status, and lymphovascular space invasion). Although RT utilization increased gradually during the study period (OR per year, 1.07), factors associated with RT were similar over time. The estimated 5-year overall survival increased significantly from 84.1% in 1994 to 2000 to 94.6% in 2005 to 2009. This population-based analysis revealed that the indications for postmastectomy RT in pT1-2N1 breast cancer in Korea are based solely on conventional anatomical factors, although their survival has increased significantly in the modern treatment era. There is a significant unmet need for better risk stratification in these patients and for tailored RT with the incorporation of tumor biology-associated factors.